2023
DOI: 10.3389/feart.2022.929271
|View full text |Cite
|
Sign up to set email alerts
|

The intensification of coastal hypoxia off central Chile: Long term and high frequency variability

Abstract: Hypoxia is a phenomenon where dissolved oxygen (DO) is reduced to levels that are low enough to strongly affect ecological and biogeochemical processes. This occurs within the continental shelf off central Chile (36°S), influenced by seasonal coastal upwelling (Spring-Summer). Monthly measurements of DO and other oceanographic variables in the water column (1997−2021) over the 92 m isobath along with high-resolution and near-surface observations (POSAR buoy), are analyzed to examine incidences of hypoxia and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Importantly, while nutrient pulses do alter phytoplankton community composition (relative abundances, e.g., Ferreira et al., 2020 ) and some macroalgal growth rates (Nielsen & Navarrete, 2004 ), no studies in Chile (or California) have unambiguously reported that seasonal variation in nutrients can propagate up the local food webs to alter species composition (through direct observations or eDNA), at least not in the better studied shallow subtidal and intertidal communities. Therefore, one of the factors that could affect the composition of invertebrates and especially fish assemblages is the frequent occurrence of hypoxic events at waters deeper than 30 and especially 60 m, that is the penetration of cold water with an oxygen level below 2 μm/L, especially in spring and summer months (De La Maza & Farías, 2023 ). Sensitivity to hypoxia varies widely among marine taxa (Diaz & Rosenberg, 1995 ; Miller et al., 2002 ; Rosenberg et al., 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, while nutrient pulses do alter phytoplankton community composition (relative abundances, e.g., Ferreira et al., 2020 ) and some macroalgal growth rates (Nielsen & Navarrete, 2004 ), no studies in Chile (or California) have unambiguously reported that seasonal variation in nutrients can propagate up the local food webs to alter species composition (through direct observations or eDNA), at least not in the better studied shallow subtidal and intertidal communities. Therefore, one of the factors that could affect the composition of invertebrates and especially fish assemblages is the frequent occurrence of hypoxic events at waters deeper than 30 and especially 60 m, that is the penetration of cold water with an oxygen level below 2 μm/L, especially in spring and summer months (De La Maza & Farías, 2023 ). Sensitivity to hypoxia varies widely among marine taxa (Diaz & Rosenberg, 1995 ; Miller et al., 2002 ; Rosenberg et al., 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the frequency and intensity of drastic dissolved oxygen decline (<20 µM O 2 ) events in many coastal marine environments have increased worldwide since the 1960s [34,[142][143][144][145]. In fact, a recent long-term study demonstrated the intensification of the hypoxia over the continental shelf off CB, where hypoxic and severe hypoxic waters (<89 and <22 µmol O 2 L −1 ) have increased more than 2-fold in volume since 1997 [146]. The projected decrease in oxygen concentrations [32] and the increase in water column stratification [33], as well as local eutrophication [34], might lead to more frequent and intense events of oxygen and other electron acceptors (e.g., NO 3 − and NO 2 − ) reduction.…”
Section: Final Considerationsmentioning
confidence: 99%
“…In the SEP, potentially observable OMZ metrics include the oxycline depth along the coast at a few sites where long-term monitoring has been performed [28][29][30] , although these coastal sites mostly sample the water column above the OMZ and may monitor anthropogenic signals from different sources difficult to interpret. Regarding relevant timescales for oxygen variability in SEP, it appears obvious to consider the interannual timescale as the El Niño Southern Oscillation (ENSO) is the main mode of interannual variability at global scale.…”
mentioning
confidence: 99%